The examination of the relationship between the neglected curriculum with emotional literacy - M.H. Mirzamohammadi, Akbar Rahnama, Mehdi Sobhaninejad, Mohammad Hasan Tajdary, (Opción, 2019)
This research aims at examining the relationship between the neglected curriculum and emotional literacy and Media Literacy. A library survey has been used to write the research literature in order to collect the required information and the field method has been used to collect experimental data on the research questions using standard questionnaires. The obtained results show that the correlation level of media literacy variable in a linear combination with the neglected curriculum is equal to 0.423, which means that there is a positive and significant relationship between the variables of the research.